Collaborative planning for development of the Pelawan Biodiversity Park in Bangka, Indonesia - DIAN AKBARINI; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2017)
Akbarini D, Iskandar J, Partasasmita R. 2017. Collaborative planning for development of the Pelawan Biodiversity Park in Bangka, Indonesia. Biodiversitas 18: 1602-1610. Pelawan Biodiversity Park is located in the village of Namang, Sub-district of Namang, District of Central Bangka. The Pelawan Biodiversity Park with a size of approximately 47 hectares is intended as a conservation area in Bangka to protect various distinctive plants and animals, especially the plant species Tristaniopsis merguensis (Griff.) Peter G.Wilson & J.T.Waterh. A preliminary review of Pelawan Biodiversity Park management planning was undertaken between January and March 2017. The purpose of this preliminary review was to obtain information for planning and managing the Pelawan Biodiversity Park which has an important function for conservation, ecotourism and research in the Central Bangka District. The method used for the study was qualitative with field data collection; namely observation, intensive interviews with informants and analysis of documentation. The results of the study show that the management planning for Pelawan Biodiversity Park has not been implemented collaboratively with stakeholders. Furthermore, the potential for biodiversity in the Palawan Biodiversity Parks has not been properly analyzed and used to develop strategies for conversation, ecotourism and research. The proposed solution to this deficiency in the planning of the Pelawan Biodiversity Park is to invite relevent stakeholders comprising village government, community leaders, universities, researchers, non-governmental organisations and private organizations to actively collaborate in the process.